Customer-Centric Healthcare System: By Integrating Intelligence into Healthcare System, to Positively Influence the Treatment Journey for Aging Population in Malaysia - Hii, Sylvia (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation investigates the integration of customer-centric healthcare solutions to address the needs of Malaysia’s rapidly aging population. With the proportion of elderly individuals rising significantly, the country faces growing challenges in delivering accessible, efficient, and culturally competent healthcare. This research aims to bridge gaps in service delivery, enhance healthcare outcomes, and empower elderly individuals to lead healthier lives. The research approach employs mixed observational methods that merge numerical questionnaire responses with interviews of healthcare providers alongside political advisers and elderly population members to assess integrated healthcare systems implementation. The study reveals three essential problems: inadequate healthcare service availability and weak provider coordination relationships and cultural resistance to healthcare innovations. Researchers explain that both social networks and healthcare providers' cultural competence play essential roles in boosting elderly well-being. This study analyzes how technology brings changes through telehealth alongside wearable devices and artificial intelligence to handle these challenges. The implementation of intelligent healthcare solutions proves beneficial for patient care delivery and enables real-time health tracking systems which supports better patient relationships particularly through their use in rural and underprivileged communities. The research development presents an extensive framework for providing integrative healthcare as it applies to Malaysia's needs for senior care. The proposed system introduces a multi-stakeholder method which highlights both government-private partnership initiatives together with health infrastructure development alongside specific policy adjustments for achieving balanced care delivery and high-quality healthcare services. This research adds value to integrated healthcare knowledge through its delivery of practical recommendations to healthcare providers and policymakers as well as researchers. The research shows that combining advanced technology with culturally appropriate healthcare practice leads to sustainable healthcare frameworks that address complexity in elderly patient needs across Malaysia. The discovered information should act as motivation for new studies that will lead to creative aging care systems which improve senior life quality.